Globalization and sovereignty beyond the territorial trap - Agnew, John A. (Lanham Rowan & Littlefield, 2018)
"This book challenges the widely accepted story that state sovereignty is in worldwide eclipse in the face of the overwhelming processes of globalization, offering a convincing framework that breaks with the either/or thinking of state sovereignty versus globalization"
Preface to the second edition -- Globalization and state sovereignty -- Sovereignty myths and territorial states -- Sovereignty regimes -- Sovereignty regimes at work -- Conclusion -- Index.
First edition published 2009.
Keywords: Sovereignty; Globalization -- Political aspects